Characterization and x-ray absorption spectroscopy of ilmenite nanoparticles derived from natural ilmenite ore via acid-assisted mechanical ball-milling process - Weerachon Phoohinkong; Sorapong Pavasupree; Anucha Wannagon; Samunya Sanguanpak; Kanokthip Boonyarattanakalin; Wanichaya Mekprasart; Wisanu Pecharapa (My University, 2017)
In this work activated ilmenite nanoparticles were prepared by chemical-assisted in mechanical ball-milling process from ilmenite ore as starting raw material. The effect of milling process on their phase composition, particle size, surface morphology and local structure were investigated. Phase identification and crystalline structure of ilmenite mineral, milled samples and subsequent leached residues were characterized by x-ray diffraction (XRD). Meanwhile, the distorted octahedral structure and the oxidation state of relevant elements in ilmenite ore and activated ilmenite obtained by different process conditions were analyzed by x-ray absorption spectroscopy (XAS). Particle size and morphologies of the samples were monitored by field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM). Three dominant peaks of TiO2 rutile, FeTiO3, and Fe2TiO4 are obviously adulterated in XRD patterns after mechanical milling with water and acid solution when comparing to precursor mineral. However, the contaminated phase of FeTiO3 and Fe2TiO4 was readily decreased by acid-assisted mechanical ball-milling. The enhancement in leaching process of ilmenite residue after milling can be obtained with sulfuric acid. This result suggests that iron contaminated phase could be leached from the sample resulting to the decrease in Fe environment around Ti atom.
Keywords: Ilmenite; Rutile; X-ray absorption spectroscopy; Extraction and Separation Processes